# 12n-2n^4-10n-2n^4+n=

## Simple and best practice solution for 12n-2n^4-10n-2n^4+n= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 12n-2n^4-10n-2n^4+n= equation:

Simplifying
12n + -2n4 + -10n + -2n4 + n = 0

Reorder the terms:
12n + -10n + n + -2n4 + -2n4 = 0

Combine like terms: 12n + -10n = 2n
2n + n + -2n4 + -2n4 = 0

Combine like terms: 2n + n = 3n
3n + -2n4 + -2n4 = 0

Combine like terms: -2n4 + -2n4 = -4n4
3n + -4n4 = 0

Solving
3n + -4n4 = 0

Solving for variable 'n'.

Factor out the Greatest Common Factor (GCF), 'n'.
n(3 + -4n3) = 0

Subproblem 1Set the factor 'n' equal to zero and attempt to solve:

Simplifying
n = 0

Solving
n = 0

Move all terms containing n to the left, all other terms to the right.

Simplifying
n = 0
Subproblem 2Set the factor '(3 + -4n3)' equal to zero and attempt to solve:

Simplifying
3 + -4n3 = 0

Solving
3 + -4n3 = 0

Move all terms containing n to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + -4n3 = 0 + -3

Combine like terms: 3 + -3 = 0
0 + -4n3 = 0 + -3
-4n3 = 0 + -3

Combine like terms: 0 + -3 = -3
-4n3 = -3

Divide each side by '-4'.
n3 = 0.75

Simplifying
n3 = 0.75

The solution to this equation could not be determined.

This subproblem is being ignored because a solution could not be determined.Solutionn = {0}`